2016
DOI: 10.1007/s00436-016-5034-1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and liver flukes of birds of prey (Accipitriformes, Falconiformes, Strigiformes) from Slovakia: uniform or diverse compound?

Abstract: During 2012-2014 up to 286 birds of the orders Falconiformes (5 species), Accipitriformes (11 species), and Strigiformes (7 species) were examined for trematodes and this represents the first detailed study in Slovakia. A total of 12 trematode species belonging to the families Diplostomidae, Cyathocotylidae, Strigeidae, and Opisthorchiidae were identified. Rare infections were found in falcons where only two species (40 %) and three of 85 examined birds (3.5 %) were infected with a low range of two to four wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…They are similar to fi ndings of Santoro et al (2012b) in Calabria (Italy) and Sanmartín et al (2004) in Galicia (Spain) who observed a relatively narrow range of helminth species within the Strigiformes family, in particular the species specifi c for owls. This is consistent with our fi ndings in owls with only two detected trematode species (Strigea strigis, Neodiplostomum canaliculatum) as was already published by Komorová et al (2016). Santoro et al (2012b) found that the helminth fauna of diurnal birds of prey is much more diverse than nocturnal birds.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…They are similar to fi ndings of Santoro et al (2012b) in Calabria (Italy) and Sanmartín et al (2004) in Galicia (Spain) who observed a relatively narrow range of helminth species within the Strigiformes family, in particular the species specifi c for owls. This is consistent with our fi ndings in owls with only two detected trematode species (Strigea strigis, Neodiplostomum canaliculatum) as was already published by Komorová et al (2016). Santoro et al (2012b) found that the helminth fauna of diurnal birds of prey is much more diverse than nocturnal birds.…”
Section: Discussionsupporting
confidence: 93%
“…In the Czech Republic, Sitko published decades-long scientifi c studies of fl ukes in diurnal (1998) and nocturnal raptors (2001). Research from the territory of Slovakia was published in the former Czechoslovakia by Ryšavý (1957) and Tenora & Lusk (1960) and comprehensive analyses of fl ukes and thorny-headed worms were published recently by us (Komorová et al, 2015;Komorová et al, 2016). Comparisons of the fl uke species spectrum in bird orders studied within our research showed certain differences between diurnal (Accipitriformes and Falconiformes) and nocturnal birds of prey (Strigiformes).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Most of the pathogens identified in this study are commonly found in European diurnal and nocturnal raptors [8,23,24,30,35,[37][38][39][40][41][42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%